1990
DOI: 10.1007/bf01537246
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to oral H2-receptor antagonists

Abstract: The acid-inhibitory action of H2-receptor antagonists was shown to decrease after one to two weeks of dosing in healthy volunteers. This tolerance was evaluated in three randomized, placebo-controlled trials with the H2-receptor antagonists famotidine, 40 mg given after the evening meal for 28 days; ranitidine, 300 mg four times a day for seven days followed by 300 mg at night until day 28; and ranitidine, 300 mg three times a day vs 300 mg at night for 14 days. Continuous 24-hr pH monitoring with glass electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 24 publications
0
71
2
Order By: Relevance
“…As already stated, although very effective in humans for treating peptic ulcers, long-term H2 antagonist treatment is complicated in some patients by the development of tolerance and recurrency (2,5,19,23,24,57). It is tempting to speculate that the inverse agonism displayed by the tested H2 antagonists, consequently resulting in an upregulation of H2 receptors, contributes to the development of tolerance after chronic treatment (2,5,19,23,24).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…As already stated, although very effective in humans for treating peptic ulcers, long-term H2 antagonist treatment is complicated in some patients by the development of tolerance and recurrency (2,5,19,23,24,57). It is tempting to speculate that the inverse agonism displayed by the tested H2 antagonists, consequently resulting in an upregulation of H2 receptors, contributes to the development of tolerance after chronic treatment (2,5,19,23,24).…”
mentioning
confidence: 96%
“…In vivo modulation of H2 receptor function after treatment of H2 antagonists has been reported (2,(19)(20)(21)(22). Prolonged H2 receptor blockade was found to result in increased parietal cell sensitivity to H2 agonists (22), increased intragastric hyperacidity after abrupt withdrawal (21), and the development of tolerance (2,5,19,23,24). Coruzzi and Bertaccini (22) and Nwokolo et al (21) hypothesized that these observations could be explained by an upregulation of H2 receptors.…”
mentioning
confidence: 96%
“…For example, the selective affinity of the inverse agonists cimetidine and metiamide for histamine H2 receptors has been linked to tolerance to H2 receptor blockade (Nwolko et al, 1990;Wilder-Smith et al, 1990;Deakin and Williams, 1992). This tolerance is believed to occur through the elevation of histamine receptor levels (Nwolko et al, 1991).…”
mentioning
confidence: 99%
“…5±7 Our study clearly showed that the marked inhibition of gastric acidity observed at day 7 with omeprazole 20 mg and 40 mg remained stable over 3 months. These data con®rmed the absence of tolerance to proton pump inhibitors contrary to H 2 -blockers 10 and the absence of a progressive increase in acid suppression despite prolonged inhibition of the proton pump. Moreover, 24-h pH pro®les remained unchanged between day 7 and day 90.…”
Section: Discussionmentioning
confidence: 64%